Vaccine-induced responses to R21/Matrix-M – an analysis of samples from a phase 1b age de-escalation, dose-escalation trial - Bundi, Caroline; Bellamy, Duncan; Kibwana, Elizabeth; Nyamako, Lydia; Ogwang, Rodney; Keter, Kelvias; Kimani, Domtila; Salman, Ahmed M.; Provstgaard-Morys, Samuel; Stockdale, Lisa; Hill, Adrian V. S.; Bejon, Philip; et al. (Frontiers in Immunology, 2025)
IntroductionThe pre-erythrocytic malaria vaccine R21 vaccine adjuvanted with Matrix-M reported good efficacy (75%) in an ongoing phase 3 trial and was recommended World Health Organization for use in children 5–36 months. Vaccine-induced antibodies against NANP are associated with protection, however, various factors such as age, pre-existing immunity, and vaccine dose have been shown to influence vaccine responses.MethodsSamples from adults (n =18), children (n = 17), and infants (n = 51) vaccinated with R21/Matrix-M in a phase I trial were assayed for vaccine-specific antibody responses. We measured antibodies (quantity) by MSD and ELISA; and function (quality) by complement (C1q) fixation assay, inhibition of sporozoite invasion (ISI) assay, and avidity assay. Pre-existing malaria antibody exposure was assessed using an anti-3D7 Plasmodium falciparum crude parasite lysate ELISA.ResultsVaccine-induced CSP antibodies (against full-length R21, NANP, and C terminus), exhibited complement fixation and inhibition of sporozoites. These were significantly lower in adults compared to children and infants. Additionally, children had a higher rate of decay of vaccine-induced antibodies compared to adults 2 years post-vaccination. Furthermore, a higher Matrix-M adjuvant dose resulted in significantly higher C1q fixation, and ISI than the low adjuvant dose in infants. Importantly, functional measures ISI and C1q-fixation were positively associated with the vaccine-induced antibodies overall, but avidity was not. Interestingly, in adults, previous malaria exposure was negatively associated with ISI but positively correlated with avidity and C1q fixation. At baseline, all the study participants were seropositive for anti-HBsAg IgG above the WHO-required protective threshold of 10 mIU/mL, and titers significantly increased post-vaccination.DiscussionR21/Matrix-M was immunogenic across all age groups, with age and vaccine dose significantly affecting antibody magnitude and function. These findings emphasize the importance of evaluating the right adjuvant and vaccine dose for clinical development progression. This could thus inform the development of next-generation malaria vaccines. However, additional crucial factors need further exploration.